Keselarasan Lembaga Penegak Hukum dalam Implementasi Restorative Justice bagi Penyalahguna Narkotika di Indonesia - Fauziah, Eva; Fatrika, Slamet; Pratiwi, Utari Dwi (UI Scholars Hub, 2022)
The problem of overcrowding of correctional institutions in Indonesia is a big problem that must be resolved immediately. The high number of Narcotics abusers who are imprisoned is the main cause of the problem. The restorative justice approach which is an alternative to sentencing that has been implemented in various countries can be an alternative in solving the problem of overcrowding in prisons. Some of the regulatory concepts for restorative justice for narcotics abusers applied in other countries include drug courts in the United States and drug diversion programs in Thailand. Various regulations have been established by the Government of Indonesia to support restorative justice programs, especially for narcotics abusers. But unfortunately, until now the program has not been able to run properly due to various problems in regulation and implementation. This study aims to describe the problems faced by Indonesia in realizing restorative justice for Narcotics abusers and provide appropriate recommendations to overcome the problems of implementing restorative justice for Narcotics abusers. The research method was carried out qualitatively by conducting a literature review of previous research, regulations, and related documents. Keywords: Overcrowding Prison, Restorative Justice, Narcotics Abusers